ADOPTION AND USAGE CONTINUITY MODEL OF ACCOUNTING MOBILE APPLICATION FOR MSMES - Darmoyo, Syarief; Weli, Weli (Journal of Accounting, Entrepreneurship and Financial Technology (JAEF), 2024)
This research explores the factors that affect the adoption of mobile accounting applications by micro-scale entrepreneurs in Indonesia. It uses the Technology Acceptance Model and Expectation-Confirmation Theory to examine how perceived strategic benefits, performance expectancy, social influence, competitive advantage, effort expectancy, facilitating conditions, and organizational readiness influence the intention to use accounting applications. The target population is Micro, Small, and Medium Enterprises (MSMEs) in Jakarta and its surrounding areas. The data collection method is a survey with a questionnaire, using convenience sampling. The data analysis method is a descriptive method with SPSS software and a structural equation model with partial least square approach with SmartPLS 3. The results show that perceived strategic benefits, performance expectancy, and social influence have a significant positive effect on the intention to use accounting applications, while the other factors do not have a significant effect. This research contributes to the literature on technology acceptance and provides practical implications for accounting application developers and MSMEs.